Burkitt lymphoma with heart involvement: features of diagnosis, treatment and follow-up - G. A. Radzhabova; I. V. Osipova; T. T. Valiev; L. R. Turkiya; L. R. Karimova; S. N. Mikhailova (Онкогематология, 2025)
Burkitt lymphoma (BL) is a highly aggressive non‑Hodgkin’s lymphoma that characterizes by affecting multiple organs and systems, which explains the diagnosis of the disease at an advanced stage upon the patient’s first medical visit. Heart involvement as part of bL dissemination is extremely rare (2–5 %), but significantly impacts the clinical course, treatment and follow‑up. Heart involvement in bL can manifest as pericardial effusion, myocardial dysfunction or subsequent development of cardiogenic shock. diagnostics of BL with heart involvement should include electrocardiography, echocardiography, N‑terminal fragment of the brain natriuretic propeptide (NT‑proBNP) blood level, myocardial damage markers (troponin I / T), and, if necessary, can include more high‑precision methods – magnetic resonance / computed tomography with intravenous contrast. Timely diagnosis and programmed treatment with rituximab can achieve long‑term survival for BL patients, including advanced stages with heart involvement.